2013
DOI: 10.1155/2013/280432
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Biologically Active Heterologous Oxalate Decarboxylase (OxdC) inLactobacillus plantarumWCFS1 Using Homologous Signal Peptides

Abstract: Current treatment options for patients with hyperoxaluria and calcium oxalate stone diseases are limited and do not always lead to sufficient reduction in urinary oxalate excretion. Oxalate degrading bacteria have been suggested for degrading intestinal oxalate for the prevention of calcium oxalate stone. Here, we reported a recombinant Lactobacillus plantarum WCFS1 (L. plantarum) secreting heterologous oxalate decarboxylase (OxdC) that may provide possible therapeutic approach by degrading intestinal oxalate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…It accumulates in the cell wall of Bacillus subtilis and can be secreted by many basidiomycetous and ascomycetous fungi [11, 12]. OxDC has garned attention due to its potentially numerous applications ranging from remediation of oxalate scaling in the wood and paper industry [13–16], bioengineering of crop plants for fungal resistance and lower oxalate content [17, 18], diagnostics and sensing of oxalate [1921], bioengineering of probiotic gut bacteria to release OxDC in the intestine [22], and as a dietary supplement for the degradation of excess oxalate in the stomach [23, 24]. Despite these efforts, significant questions remain about the details of the enzymatic mechanism of OxDC, and in particular about how modifications of the enzyme can direct its chemistry away from decarboxylase to oxidase activities [25].…”
Section: Introductionmentioning
confidence: 99%
“…It accumulates in the cell wall of Bacillus subtilis and can be secreted by many basidiomycetous and ascomycetous fungi [11, 12]. OxDC has garned attention due to its potentially numerous applications ranging from remediation of oxalate scaling in the wood and paper industry [13–16], bioengineering of crop plants for fungal resistance and lower oxalate content [17, 18], diagnostics and sensing of oxalate [1921], bioengineering of probiotic gut bacteria to release OxDC in the intestine [22], and as a dietary supplement for the degradation of excess oxalate in the stomach [23, 24]. Despite these efforts, significant questions remain about the details of the enzymatic mechanism of OxDC, and in particular about how modifications of the enzyme can direct its chemistry away from decarboxylase to oxidase activities [25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly a novel Ll.LtrB intron expression plasmid (pLpACD4C) created in this study can be useful for gene targeting in L. plantarum WCFS1. Previously, heterologous oxalate decarboxylase was expressed in L. plantarum and preliminary results suggested that usage of recombinant L. plantarum prevent the calcium oxalate stone formation in rats . The genetically modified lactic acid bacterium developed in this study with its biological containment status will be used as probiotic tools to deliver oxalate decarboxylase into the human intestine for the prevention of hyperoxaluria and renal stone disease in future.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, recombinant Lactobacillus plantarum ( L. plantarum ) has been developed for delivery of heterologous oxalate decarboxylase for the prevention of CaOx urolithiasis and the administration of recombinant L . plantarum prevents the enteric hyperoxaluria in experimental rats .…”
Section: Introductionmentioning
confidence: 99%
“…; Sasikumar et al . ), the identification of the mutations would require whole‐genome sequencing of the mutants and of the wild‐type, which is beyond the scope of this work. The mutant C17‐m58 has been selected for further comparative studies (chemostat cultivation in defined composition medium) to clarify some metabolic aspects about respiration in Lact.…”
Section: Discussionmentioning
confidence: 99%